Immune complex mediated lung haemorrhage and nephritis--successful treatment with plasma exchange, haemodialysis and immunosuppressive drug therapy. Issue 699 (January 1984) - Drew, P. J.; Newland, A. C.; Marsh, F. P.
Abstract : A 16-year-old boy developed an immune complex illness associated with lung haemorrhage, proliferative nephritis with crescents and renal failure. Treatment with plasma exchange, haemodialysis and immunosuppressive drugs resulted in a rapid reduction in levels of immune complexes and other mediators of inflammation and was associated with good recovery of renal and lung function. Subsequently, deterioration in renal function occurred whilst the patient was on treatment with prednisolone alone but this was reversed with a short course of plasma exchange and the addition of azathioprine. No further deterioration in renal or lung function has been observed during 18 months treatment with azathioprine and prednisolone. Immediate plasma exchange and immunosuppressive drug treatment have been recommended for Goodpasture's syndrome. Immune complex mediated lung haemorrhage and nephritis is the main clinical differential diagnosis. Our case suggests that the same treatment is effective for both conditions if given early, and that detailed renal and immunological investigations should not be allowed to delay this.